Development and optimization of near-IR contrast agents for immune cell tracking - Joshi, Pratixa P. (Optical Society of America, 2013)
Gold nanorods (NRs) are attractive for in vivo imaging due to their high optical cross-sections and tunable absorbance. However, the feasibility of using NRs for cell tracking has not been fully explored. Here, we synthesized dye doped silica-coated NRs as multimodal contrast agents for imaging of macrophages – immune cells which play an important role in cancer and cardiovascular diseases. We showed the importance of silica coating in imaging of NR-labeled cells. Photoacoustic (PA) imaging of NRs labeled macrophages showed high sensitivity. Therefore, these results provide foundation for applications of silica-coated NRs and PA imaging in tracking of immune cells.